Network orchestration for value platform development - Perks, Helen; Kowalkowski, Christian; Witell, Lars; Gustafsson, Anders (Elsevier, 2017)
The traditional firm and product-centric view of platforms is changing. Platforms are increasingly developed around value that is co-created with a network of actors. In such settings, lead firms shape their environments and develop value platforms through network orchestration. This study examines how lead firms mobilize network relationships to support and build novel value platforms. The research adopts a multiple case study methodology, investigating the development of six value platforms in network settings within Europe. A large-scale interview program over several years was conducted. The findings unravel practices constituting four overarching network orchestration mechanisms in the value platform development context; envisioning, inducing innovativeness, legitimizing, and adjusting. The study explains the relationships and interplay between the orchestration mechanisms and articulates theoretical and managerial contributions.